Glucuronides of phytoestrogen flavonoid enhance macrophage function via conversion to aglycones by β‐glucuronidase in macrophages. Issue 3 (8th May 2017) - Kaneko, Atsushi; Matsumoto, Takashi; Matsubara, Yosuke; Sekiguchi, Kyoji; Koseki, Junichi; Yakabe, Ryo; Aoki, Katsuyuki; Aiba, Setsuya; Yamasaki, Kenshi
Abstract: Introduction: Flavonoids are converted to inactive metabolites like glucuronides in the gut, and circulate mainly as glucuronides in blood stream, resulting in low concentrations of active aglycones in plasma. It is therefore unclear how oral flavonoids exert their effects in tissues. We recently reported the plasma pharmacokinetics of some flavonoids and suggested the possibility that the absorbed flavonoids modified macrophage functions leading to enhance bacterial clearance. We aimed to confirm their pharmacological profiles focusing on tissue macrophages. Methods: Pseudoinfection was induced by intradermal injection of FITC‐conjugated and killed Staphylococcus aureus into the ears of mice treated with or without genistein 7‐ O ‐glucuronide (GEN7G, 1 mg/kg, i.v.). FACS analysis was performed on single cell suspensions dispersed enzymatically from the skin lesions at 6 h post pseudoinfection to evaluate phagocytic activities of monocytes/macrophages (CD11b + Ly6G − ) and neutrophils (CD11b + Ly6G + ). Phagocytosis of the FITC‐conjugated bacteria by four glucuronides including GEN7G was evaluated in cultures of mouse macrophages. Results: After GEN7G injection, genistein was identified in the inflamed ears as well as GEN7G, and the phagocytic activity of CD11b + Ly6G − cells was increased. GEN7G was converted to genistein by incubation with macrophage‐related β‐glucuronidase. Macrophage culture assays revealed that GEN7G increased phagocytosis, and the action was dampened by a β‐glucuronidase inhibitor. Binding of aglycones to estrogen receptors (ERs), putative receptors of flavonoid aglycones, correlated to biological activities, and glucuronidation reduced the binding to ERs. An ER antagonist suppressed the increase of macrophage function by GEN7G, whereas estradiol enhanced phagocytosis as well. Conclusions: This study suggests a molecular mechanism by which oral flavonoids are carried as glucuronides and activated to aglycones by β‐glucuronidase in tissue macrophages, and contributes to the pharmacological study of glucuronides. Abstract : This study suggests a molecular mechanism by which oral flavonoids activate tissue macrophages, and contributes to the pharmacological study of glucuronides.